Development of patch stack antenna for CP-SAR sensor - Muhammad Fauzan Edy Purnomo; Vita Kusumasari; Rusmi Ambarwati; Sigit Kusmaryanto; Sholeh Hadi Pramono; Dwi Fadila Kurniawan; Akio Kitagawa (Bulletin of Electrical Engineering and Informatics, 2021)
In this paper, we obtain the basic configuration of the left-hand circular polarization (LHCP) array two patches stack triangular truncated microstrip antenna. This construction use the basic corporate feed microstrip-line with modified lossless T-junction power divider on radiating patch for circularly polarized-synthetic aperture radar (CP-SAR) sensor embedded on airspace with compact, small, and simple configuration. The design of Circular Polarization (CP) is realized by truncating the whole three tips and adjusting the parameters of antenna at the resonant frequency, f=5.2 GHz. The results of characteristic performance and S-parameter for the LHCP array two patches stack antenna at the resonant frequency show successively about 7.24 dBic of gain, 1.99 dB of axial ratio (Ar), and -11.43 dB of S-parameter. Moreover, the impedance bandwidth and the 3 dB-Ar bandwidth of this antenna are around 560 MHz (10.77%) and 50 MHz (0.96%), respectively.